Analisis Saluran Pemasaran Buah Naga (Hyilocereus Polyrhizus) Di Desa Taratak Nagodang Kecamatan Ujung Padang Kabupaten Simalungun - Aulia, Endang Sri; Wahyuni, Sri; Yani, Farida (Universitas Medan Area, 2023)
Taratak Nagodang Village, Simalungun Regency is one of the dragon fruit producing villages in Ujung Padang District, Simalungun Regency, which has been cultivated by 45 farmers. The problems in this village are the lack of extensive marketing network and the weak bargaining position of farmers at harvest time. The purpose of this study was to determine the dragon fruit marketing channels, the amount of margin received by each marketing channel and the marketing efficiency of dragon fruit in Taratak Nagodang Village, Ujung Padang District, Simalungun Regency. The research was conducted in Taratak Nagodang Village by taking a sample of 16 people. The analytical method used is the formula: Margin: HP – HB and the efficiency formula: Ep = (TB/TNB) × 100%. Based on the results of the study it was concluded that there were 2 (two) marketing channels for dragon fruit that occurred in Taratak Nagodang Village, namely, the first channel: farmers consumers and the second channel: farmers collectors retailers consumers. The margin obtained in the first channel is Rp. 0,- and the margin obtained in the second channel is Rp. 8.000,-/Kg. Of the two marketing channels, the farmer's share obtained for the first marketing channel is 100% and for the second channel the farmer's share is 64.7% so that the first channel is more efficient because it is higher than the second marketing channel, even though the marketing channel one is more efficient, but in fact the marketing channel the second is more chosen by dragon fruit farmers in the village of Taratak Nagodang because it is faster in the sales process and does not want to bear the risk of losses for storage costs.